Contribuição ao estudo dos valores normais de hemograma de cutias Dasyprocta azarae Lichtenstein, 1823 (Dasyproctidae, Mammalia) - Mangrich-Rocha, Rita Maria Venancio (2000)
Orientador: Pedro Ribas Werner